WISATA BUMI PERKEMAHAN KABUPATEN KUBU RAYA - Cesadhea, Alfreda; Khaliesh, Hamdil; BR Gultom, Bontor Jumaylinda (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Scouting activities are established as mandatory activities in every school in West Kalimantan. Scout activities are inseparable from camp activities. Camp activities require facilities or containers to house these activities. However, camp facilities in West Kalimantan are still minimal and some are inadequate. The Kubu Raya Regency government is preparing to build a campground and urban forest tourism centered in Limbung, Sungai Raya District. The local government is also maximizing the tourism aspect in accordance with Kubu Raya Regency Regional Regulation Number 17 of 2017. The basic purpose of this design is to produce a design regarding campground tourism in Kubu Raya Regency which can accommodate scouting and similar activitie accompanied by tourist attractions. The stages of the design process are carried out by collecting data, analyzing and synthesizing, and the design stage. The concept of the resulting design area is in the form of a function concept so that the resulting design area is divided into a reception zone, recreation zone, management zone, and camp zone. The circulation of the area consists of pedestrian and vehicle circulation and uses boundary, directional, shading, and ornamental vegetation. The building mass is placed in each zone according to its function and is made with the same characteristics to create an image of the area as well as a form that follows the concept of function and the use of natural colors in the building gives a natural impression resembling natural conditions. The structure of the lower part of the building uses a pile foundation, the middle structure uses a concrete structure, the upper structure uses light steel, adjusting to existing conditions and space functions.